2004
DOI: 10.1261/rna.5241404
|View full text |Cite
|
Sign up to set email alerts
|

Premature termination codons do not affect the rate of splicing of neighboring introns

Abstract: Introduction of a premature termination codon (PTC) into an exon of a gene can lead to nonsense-mediated decay of the mRNA, which is best characterized as a cytoplasmic event. However, increasing evidence has suggested that PTCs may also influence the nuclear processing of an RNA transcript, leading to models of nuclear surveillance perhaps involving translating nuclear ribosomes. We used quantitative RT-PCR to measure the in vivo steady-state levels of every exon-intron junction in wild-type, PTC-containing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…They showed that the size of the PTC+ focus was larger than that of the PTC− focus and suggested that this effect is due to PTC+ pre-mRNA accumulation at the site of transcription. However, we see no difference in focus size by FISH when examining single integrants of PTC+ and PTC− reporter genes in yeast, consistent with a PTC-independent explanation for this phenomenon (Lytle and Steitz 2004). Since there is also no observable PTC effect on nuclear-retained mRNAs by biochemical criteria, we conclude that the transcription-site foci of PTC− and PTC+ reporters are comparable.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They showed that the size of the PTC+ focus was larger than that of the PTC− focus and suggested that this effect is due to PTC+ pre-mRNA accumulation at the site of transcription. However, we see no difference in focus size by FISH when examining single integrants of PTC+ and PTC− reporter genes in yeast, consistent with a PTC-independent explanation for this phenomenon (Lytle and Steitz 2004). Since there is also no observable PTC effect on nuclear-retained mRNAs by biochemical criteria, we conclude that the transcription-site foci of PTC− and PTC+ reporters are comparable.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, other observations in mammalian systems have shown that a PTC can affect specific nuclear events, such as alternative splicing and 3 end formation (Brogna 1999;Wang et al 2002). Muhlemann and colleagues (2001) further demonstrated by fluorescent in situ hybridization (FISH) that pre-mRNAs accumulate in larger transcriptionsite foci from integrated PTC-containing reporter genes, although this interpretation has been recently questioned as being due to NMD-independent events (Lytle and Steitz 2004). Taken together, the results indicate that a PTC can affect features of RNA metabolism, within or associated with mammalian nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The RNase protection protocol was adapted from one published earlier (45) and is described in detail in SI Materials and Methods and elsewhere (51).…”
mentioning
confidence: 99%
“…As splicing is a nuclear event -much of it occurring co-transcriptionally (see below) -this also implies that detection must take place close to the transcription site (Wilkinson and Shyu, 2002;Vasudevan and Peltz, 2003). However, recent work suggests that the effects may not be as large as originally suspected (Lytle and Steitz, 2004).…”
mentioning
confidence: 99%